Toward Sustainability: Bike-Sharing Systems Design, Simulation and Management - Caggiani, Leonardo; Camporeale, Rosalia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The goal of this Special Issue is to discuss new challenges in the simulation and management problems of both traditional and innovative bike-sharing systems, to ultimately encourage the competitiveness and attractiveness of BSSs, and contribute to the further promotion of sustainable mobility. We have selected thirteen papers for publication in this Special Issue.